2023
DOI: 10.2174/1874467215666221005115007
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of Diterpenes over Innate Immunity and Cytokine Production in a Human Alveolar Epithelial Cell Line Infected with Mycobacterium tuberculosis

Abstract: Background: Mexico has the largest number of the genus salvia plant species, whose main chemical compounds of this genus are diterpenes, these chemical compounds have shown important biological activities such as: antimicrobial, anti-inflammatory and immunomodulatory. Objective: This study aimed to evaluate the immunomodulatory activity of three diterpenes: 1) icetexone, 2) anastomosine and 3) 7,20-dihydroanastomosine, isolated from Salvia ballotiflora, over innate immunity and cytokine production in a human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Likewise, the role of medicinal plants and their bioactive derivatives as alveolar NLRP3 inflammasome regulators during M. tuberculosis infection was explored, providing information about the mechanism in which they can inhibit excessive stimulation of the inflammasomes and its associated factors, and as a consequence reducing immunopathological response in the host (Mvubu & Chiliza, 2021). Later, the immunomodulatory activity of some diterpenes was confirmed in a human alveolar epithelial cell line infected with M. tuberculosis (Hernández-Herrera et al, 2023), while sinaphyl alcohol diacetate and ergosterol peroxide were proved to reduce interleukin-12 levels and Toll-like receptor-2 protein expression, and to increase the human leucocyte antigen-DR protein expression in diabetic patients with tuberculosis The other aspect related to antituberculosis immune response is the state of microbiota. Studies have shown that subjects suffering from tuberculosis and treated with classical drug regimens can have the impaired balance of intestinal flora.…”
Section: Therapy Adjuvantsmentioning
confidence: 99%
“…Likewise, the role of medicinal plants and their bioactive derivatives as alveolar NLRP3 inflammasome regulators during M. tuberculosis infection was explored, providing information about the mechanism in which they can inhibit excessive stimulation of the inflammasomes and its associated factors, and as a consequence reducing immunopathological response in the host (Mvubu & Chiliza, 2021). Later, the immunomodulatory activity of some diterpenes was confirmed in a human alveolar epithelial cell line infected with M. tuberculosis (Hernández-Herrera et al, 2023), while sinaphyl alcohol diacetate and ergosterol peroxide were proved to reduce interleukin-12 levels and Toll-like receptor-2 protein expression, and to increase the human leucocyte antigen-DR protein expression in diabetic patients with tuberculosis The other aspect related to antituberculosis immune response is the state of microbiota. Studies have shown that subjects suffering from tuberculosis and treated with classical drug regimens can have the impaired balance of intestinal flora.…”
Section: Therapy Adjuvantsmentioning
confidence: 99%